Novel fully-BODIPY functionalized cyclotetraphosphazene photosensitizers having high singlet oxygen quantum yields - Senkuytu, Elif; Ecik, Esra Tanriverdi (Pergamon-Elsevier Science Ltd, 2017)
Novel fully-BODIPY functionalized dendrimeric cyclotetraphosphazenes (FBCP 1 and 2) have been synthesized and characterized by H-1, C-13 and P-31 NMR spectroscopies. The photophysical and photochemical properties of FBCP 1 and 2 are investigated in dichloromethane solution. The effectiveness of singlet oxygen generation was measured for FBCP 1 and 2 by UV-Vis spectra monitoring of the solution of 1,3-diphenylisobenzofuran (DPBF), which is, a well-known trapping molecule used in detection of singlet oxygen. FBCP 1 and 2 show high molar extinction coefficients in the NIR region, good singlet oxygen quantum yields and appropriate photo degradation. The data presented in the work indicate that the dendrimeric cyclotetraphosphazenes are effective singlet oxygen photosensitizers that might be used for various areas of applications such as photodynamic therapy and photocatalysis. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cyclotetraphosphazene; BODIPY; Photosensitizers; NMR